Bulk polycrystalline ceria–doped Al2O3 and YAG ceramics for high-power density laser-driven solid-state white lighting: Effects of crystallinity and extreme temperatures. Issue 8 (28th April 2020) - Penilla, Elias H.; Sellappan, Pathikumar; Duarte, Matthew A.; Wieg, Andrew T.; Wingert, Matthew C.; Garay, Javier E.
Abstract: Abstract : Here, we develop and characterize high thermal conductivity/high thermal shock-resistant bulk Ce-doped Al2 O3 and propose it as a new phosphor converting capping layer for high-powered/high-brightness solid-state white lighting (SSWL). The bulk, dense Ce:Al2 O3 ceramics have a 0.5 at.% Ce:Al concentration (significantly higher than the equilibrium solubility limit) and were produced using a simultaneous solid-state reactive current activated pressure-assisted densification (CAPAD) approach. Ce:Al2 O3 exhibits a broadband emission from 400 to 600 nm, which encompasses the entire blue and green portions of the visible spectrum when pumped with ultraviolet (UV) light that is now commercially available in UV light–emitting devices and laser diodes (LD). These broadband phosphors can be used in the commonly used scheme of mixing with other UV-converting capping layers that emit red light to produce white light. Alternatively, they can be used in a novel composite down-converter approach that ensures improved thermal–mechanical properties of the converting phosphor capping layer. In this configuration, Ce:Al2 O3 is used with proven phosphor conversion materials such as Ce:YAG as an active encapsulant or as a capping layer to produce SSWL with an improved bandwidth in the blue portion of the visible spectrum. To study the effect of crystallinity on the Ce photoluminescent (PL) emission, we synthesize Ce:YAG ceramics using high-pressure CAPAD at moderate temperatures to obtain varying crystallinity (amorphous through fully crystalline). We investigate the PL characteristics of Ce:Al2 O3 and Ce:YAG from 295 to 4 K, revealing unique crystal field effects from the matrix on the Ce dopants. The unique PL properties in conjunction with the superior thermal–mechanical properties of Ce:Al2 O3 can be used in high-powered/high-brightness–integrated devices based on high-efficiency UV-LD that do not suffer efficiency droop at high drive currents to pump the solid-state capping phosphors.